Agriculture Crop Recommendation Based On Productivity And Seasons - Tomar, Ankur; Ghosh, Subhajit (Journal of Neonatal Surgery, 2025)
The crop recommendation model was trained using a structured dataset containing key agronomic and environmental parameters. As shown in Figure 3, the dataset includes nitrogen (N), phosphorus (P), potassium (K), temperature, humidity, rainfall, and soil pH as input features. The output label indicates the most suitable crop for the given set of conditions. This data forms the foundation for developing the machine learning model used in this study. In Meerut, many people are farmers. Farming is how they grow food and earn money. But to grow more food, it is very important to choose the right crop for the right season. Sometimes, farmers don’t know which crop is best to grow in the weather and soil of their area. We collected old data about crops, soil, and weather in Meerut. Then we used smart computer programs to study this data and find out which crops grow best in each season. Our system gives suggestions to farmers about the best crop to grow in each season. This helps them grow more food with less effort and earn more money. It makes farming simpler and better for the people of Meerut.